Parenting Patterns' Influence on Children's Socio-Emotional Growth in Sumuran Village: Role of Education - Kosasih, Shinta Fitriani; Ritonga, Hasnun Jauhari (UIN Sultan Aji Muhammad Idris Samarinda, 2024)
Social emotional development in elementary school age children needs to receive appropriate treatment so that they can develop optimally. The most important thing is the parenting style that parents apply to their children. This research aims to analyze the relationship between parenting and children's social emotional development in terms of parents' educational background. This research applies qualitative methods, data was collected through in-depth interviews with 5 parents who had not graduated from high school, 2 children in grade 6 of elementary school and participant observation in 2 families. The results of the research show that the parenting style of parents who did not graduate from high school has several characteristics, namely: (1)dominant authoritarian parenting style, and (2)lack of effective communication. Such communication patterns can have a negative impact on children's socio-emotional development, including: (1)low self-confidence,(2)difficulty processing emotions and (3)lack of social skills. This writing recommends several methods to improve parenting communication patterns for parents who have not graduated from high school, namely: (1)following child-friendly parenting training based on the Quran and (2)persuasive communication patterns to improve children's discipline. This writing is expected to contribute to improving theoretical and applicable understanding in supporting the quality of child care, especially for children raised by parents who have not graduated from high school in Sumuran village,South Tapanuli district.